Time schedule for operation "Sea Eagle." (1943)
Time schedule for the 210th Infantry Division operation "Sea Eagle." Taken from microfilm Records of the German Field Command, Armies, National Archives Series T-315, Reel 1621, Annex 2, KTB No. 3 , 210 Infantry Division, folder 45787/2, first frame 000237. Translated by Major James F. Gebhardt, USA (retired)